Harmony in hectic: Exploring the relationship between work-life balance and working mothers' happiness through self esteem as mediator - Murniasih, Farhanah; Hamid, Abdul (Universitas Mercu Buana Yogyakarta, 2025)
Social changes have transformed the role of a mother, leading many to pursue professional paths, often posing challenges in balancing work and personal well-being. The objective of this study was to examine the role of self-esteem in the relationship between work-life balance (WLB) and the happiness of working mom. This research used a quantitative approach. The respondents of this study were 200 working mothers aged 21 to 64 years who lived in the Greater Jakarta area. The sampling technique was purposive sampling. The measurement instruments used in this study consisted of the Oxford Happiness Questionnaire, the Rosenberg Self-Esteem Scale (RSES), and the Work-Life Balance Scale. The research hypothesis was tested using Macro PROCESS v4.3 by Hayes. The research revealed that work-life balance significantly impacts the happiness of working mothers and self-esteem acts as a mediator between work-life balance and happiness. These findings indicated that a healthy work-life balance leads to increased satisfaction, acceptance, and self-esteem. High self-esteem individuals feel capable, meaningful, and valuable, leading to a positive affect and a better quality of life, which are the sources of happiness.